Multiple Upward Residual Gravity and Magnetic Maps to Estimate the Deep Crustal Layers and Moho Discontinuity in Eastern Iraq - Al-Banna, Ahmed Sh.; Majeed, Hayder H. (Iraqi Journal of Science, 2024)
The upward continuation technique was applied to the gravity and magnetic data to obtain the residual anomalies maps in eastern Iraq. A new processing method is introduced to calculate the crustal layers depending on the relation between the total range of the residual anomalies of gravity, magnetic data and the upward continuation, with multi-elevations. The significant relationship shows slope variations, which may reflect the maximum contrast in the physical properties (density and/or susceptibility) and the intersection point representing the depth of layer contacts. This method was applied to the eastern central part of Iraq, adjacent to the Iranian borders. It is found that the average depth range to the Jurassic formations, top basement rocks, transition layer (Curie point), and Moho discontinuity are 3.1- 4.8 km, 8-12.9 km, 20.9-22.4 km and 43.6 km, respectively. The Sedimentary cover in the study area ranges from 8 to 13 km. The maximum depth to the Moho discontinuity obtained by gravity data in the study area is 43.6 km. The radially average power spectrum technique was applied in the study area to calculate the gravity depth and magnetic sources’ depth. Three depth levels of sources from gravity and magnetic data were obtained. These depths are shallow sources, average basement rock and deep sources (Moho) at 3km, 13.2-12.1 km, and 32.2-34km, respectively. The obtained results concerning the main layers in the crust were compared between the two methods, and the new method shows more reliable results. The detected depth levels refer to top Jurassic, basement rocks, and Moho discontinuity. The new method is believed to be used to detect the crustal layers depth with good results.